ANTIBACTERIAL ACTIVITY OF SILVER IONS WHEN INCORPORATED IN FILTERS OF COMPOSITES FOR SECONDARY CARIES PROTECTION- A SYSTEMATIC REVIEW - Elakiya S,; Dinesh Dhamodhar,; Prabu D,; Rajmohan M,; Bharathwaj V V,; Sindh R,; Gousalya V, (EPRA International Journal of Multidisciplinary Research (IJMR), 2022)
To determine the antibacterial activity of silver ions while incorporating with filters of composite resins for the protection of secondary caries. A systematic review was conducted based on a literature search using the search keywords (antibacterial activity) AND (composite resin) AND (secondary caries). An in-vitro study investigating the antibacterial activity of silver ions while incorporating composite resins for the protection of secondary and further followed by Cochrane database bias assessment was done. Eight in-vitro studies were included. The results of all eight studies were statistically significant with the antibacterial activity of silver ions with composite resins and protection of secondary caries. This study concludes that there is an effective antibacterial activity of silver ions while incorporated with the composite filling for the protection of secondary caries. All the study concludes there is a significant between the protection of secondary caries while filled with composite resin and antibacterial activity.